New Approach for Common Fixed Point Theorems via C-Class Functions in Gp-Metric Spaces - A. H. Ansari; M. A. Barakat; H. Aydi (Journal of Function Spaces)
We prove a new approach for some common fixed point results in complete Gp-metric spaces for weakly increasing self-mappings satisfying ψ,φ-contractions via the concept of C-class functions. An example is also provided.